2022
DOI: 10.3390/biology11081122
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Exposure to Ozone and Fine Particulate Matter and Risk of Premature Coronary Artery Disease: Results from Genetics of Atherosclerotic Disease Mexican Study

Abstract: (1) Background: Epidemiological studies have identified associations between fine particulate matter (PM2.5) and ozone exposure with cardiovascular disease; however, studies linking ambient air pollution and premature coronary artery disease (pCAD) in Latin America are non-existing. (2) Methods: Our study was a case–control analysis nested in the Genetics of Atherosclerotic Disease (GEA) Mexican study. We included 1615 participants (869 controls and 746 patients with pCAD), recruited at the Instituto Nacional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Chen et al [ 25 ] in their analysis found increased mortality related to PM2.5 air pollution. In the analysis of Pasada-Sanchez et al [ 26 ], ozone and PM2.5 exposure were found associated with premature coronary artery disease in metropolitan areas.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [ 25 ] in their analysis found increased mortality related to PM2.5 air pollution. In the analysis of Pasada-Sanchez et al [ 26 ], ozone and PM2.5 exposure were found associated with premature coronary artery disease in metropolitan areas.…”
Section: Discussionmentioning
confidence: 99%
“…When we unconsciously expose to a widely spread PM 2.5 through different routes in daily life, such as inhalation, skin, and ocular transportation (Morawska et al, 2017), PM 2.5 can make hazard risks when entering the circulation system after exposure. Epidemiologic studies have shown that PM 2.5 exposure can associate with various diseases in the respiratory and cardiovascular systems, especially asthma (Liu, Pan, et al, 2019; R. Zheng et al, 2022), bronchitis (Horne et al, 2018), and coronary artery disease (Kaufman et al, 2016; Posadas‐Sanchez et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic studies have shown that PM 2.5 exposure can associate with various diseases in the respiratory and cardiovascular systems, especially asthma (Liu, Pan, et al, 2019;R. Zheng et al, 2022), bronchitis (Horne et al, 2018), and coronary artery disease (Kaufman et al, 2016;Posadas-Sanchez et al, 2022).…”
Section: Introductionmentioning
confidence: 99%